Peran Bank Syariah dalam Menegakkan Mutual Benefit: Hybrid Contract pada Produk Qardh Beragun Emas - Afani Adam, Muhammad; Habibi, Ahmad; Shafira, Alfina; Dewi Santi, Asmita; Kurniawan, Hafidz; Nita Susanti, Dian (Al-Mashrof: Islamic Banking and Finance, 2021)
ABSTRACTThe existence of Islamic banks was initially driven by the desire for the availability of financial services in accordance with Islamic principles by realizing a banking system that avoided the practice of interest (which is considered synonymous with usury), gambling (maysir), and uncertainty (gharar) and other practices that are not in line with Islamic principle. This study used the descriptive qualitative method. This study aims to determine the role of Islamic Banks in channeling financing through mutual benefits such as savings, current accounts, and deposits. The results of this study found that Islamic banks have contributed to providing financing that can increase people’s purchasing power through the concept of Mutual Benefit. As for the hybrid contracts contained in the gold-backed qardh products, they are included in the mujtami’ah group, not mutaqabalah because there are no requirements and linkages between one contract and another.